Imaging biological surface topography in situ and in vivo. Issue 11 (8th May 2017) - Wainwright, Dylan K.; Lauder, George V.; Weaver, James C.
Summary: The creation of accurate three‐dimensional reconstructions of biological surfaces is often challenging due to several inherent limitations of current imaging technologies. These include the inability to image living material, requirements for extensive specimen preparation and/or long image acquisition times, and the inability to image at length scales that are relevant for the study of interfacial phenomena that occur between the organism and its environment. In this paper, we demonstrate the use of a new imaging approach that combines the benefits of optical and contact profilometry to image organismal surfaces quickly and without the need for any kind of specimen preparation, thus permitting three‐dimensional visualization in situ . As a proof of concept, we demonstrate the utility of this approach by imaging the surfaces of a wide range of live and preserved fish and other species, imaging wet, mucus‐covered surfaces, and presenting quantitative metrics of surface roughness in a variety of natural and engineered materials. Given the numerous wet, sticky, and slimy surfaces that abound in nature and the importance of the interface between species and their environments for the study of numerous biophysical phenomena, we believe this approach holds considerable promise for providing new insights into surface structural complexity in biological systems.